Evaluating the Use of Teach-Back in Simulation Training to Improve Discharge Communication Practices of Undergraduate Nursing Students - MacLean, S.; Kelly, Michelle; Geddes, F.; Della, Phillip (Elsevier Inc., 2018)
© 2018 International Nursing Association for Clinical Simulation and Learning Background: This study evaluates the effectiveness of information- and interaction-based training interventions to improve nurses’ communication skills during the discharge of a patient. Method: A quasi-experimental control group design was applied. Students demonstrated their discharge skills with simulated patients (SPs) in three randomly assigned groups namely control, information-, and interaction-based intervention. An independent group multivariate analyses of variance was used for analysis of both the quality of discharge content and delivery across groups using student, SP, and faculty assessor ratings. Results: Significant incremental improvements in student communication skills were achieved in the interaction and information groups compared with the control group. Conclusion: A structured curriculum including high-fidelity simulation, with SPs providing feedback and evaluating students’ information- and interaction-based communication skills, is useful in improving student discharge practices and “patients'” understanding of discharge instructions.